Towards understanding and managing the politics of tourism in a crisis-challenged world - Freya Higgins-Desbiolles; Raoul Bianchi (Annals of Tourism Research Empirical Insights)
This article offers an overview of the literature and state of knowledge on the politics of tourism. While the politics of tourism remains an under studied topic in tourism academia, here we argue political analyses are vital for advancing our understanding of the deep-rooted dynamics of tourism and how we respond to arising crises.We analyze the interface between tourism and politics, briefly outline key contemporary issues and introduce some new vistas for future inquiries. The foundation of the politics of tourism is a search for the good life and critical questions arise including democratic participation, neoliberalizing forces and possibility of diverse worldviews challenging neoliberal domination. This article serves as an introduction to a curated collection.